Positivity of Fundamental Matrix and Exponential Stability of Delay Differential System - Alexander Domoshnitsky; Roman Shklyar; Mikhail Gitman; Valery Stolbov (Abstract and Applied Analysis)
The classical Wazewski theorem established that nonpositivity of all nondiagonal elements pij  (i≠j,  i,j=1,…,n) is necessary and sufficient for nonnegativity of the fundamental (Cauchy) matrix and consequently for applicability of the Chaplygin approach of approximate integration for system of linear ordinary differential equations xi′t+∑j=1n‍pijtxjt=fit,   i=1,…,n. Results on nonnegativity of the Cauchy matrix for system of delay differential equations xi′t+∑j=1n‍pijtxjhijt=fit,   i=1,…,n, which were based on nonpositivity of all diagonal elements, were presented in the previous works. Then examples, which demonstrated that nonpositivity of nondiagonal coefficients pij is not necessary for systems of delay equations, were found. In this paper first sufficient results about nonnegativity of the Cauchy matrix of the delay system without this assumption are proven. A necessary condition of nonnegativity of the Cauchy matrix is proposed. On the basis of these results on nonnegativity of the Cauchy matrix, necessary and sufficient conditions of the exponential stability of the delay system are obtained.